Dissecting implementation musharakah in Islamic bank in Indonesia: a case study - Inten Meutia; Mohamad Adam (Jurnal Akuntansi dan Auditing Indonesia, 2017)
This study aims to analyze whether musharakah financing applications implemented by Islamic banks in Indonesia have met the requirements of Sharia standards as stipulated in the National Sharia Council Fatwa (DSN) Number 8, Sharia Accounting Standard Number 106 and Financial Accounting Standards (FAS) Number 4. This research used a case study approach that analyzes the case of musharakah in one of Islamic banks. This study found the existence of Islam in practice deviated from the paradigm of profit sharing. Calculations for results on musharakah financing tend to determine the fixed amount in advance. The portion of profit sharing is determined largely by the amount of funds provided by the bank, not those set by PSAS Number 106 or FAS Number 4.